Capital Market Development in a Small Country : The Case of Slovenia - Andritzky, Jochen (IMF Working Papers; Working Paper ;, 2007)
Small emerging economies, despite their significant growth, lack the scale to develop thriving capital markets from their local investor and issuer base that are able to deliver the benefits of a large, mature market. Slovenia is such an example. Despite the necessary infrastructure in place, trading has remained thin and issuance activity has been dormant. This paper proposes a two-pronged strategy for capital market development that leverages the existing setup in the context of regional integration such as within the EU. While using the case of Slovenia, this path might be indicative for other small countries that are part of a larger economically integrated region.